Highly Recommended? How Relation-Specific Attachment Styles Bias Customers Willingness to Recommend - Verbeke, Willem J. M. I.; Gijsenberg, Maarten J.; Hendriks, Larissa M. E.; Bouma, Jelle T.; Teunter, Linda H. (Frontiers in Psychology, 2020)
As concepts from attachment theory are increasingly being applied to business situations, we examine how relationship-specific (RS) versus general (G) attachment styles affect customers’ willingness-to-recommend (WtR). WtR refers to the likelihood of customers to recommend the services of their service provider to other customers on the basis of their experiences with the provider. WtR is often measured by means of the net promoter score (NPS), which is assumed to be a reliable (credible) market signal because it originates from customers themselves and not from the firm. This study draws on data from 798 members of an online panel from the Netherlands covering four service industries, who were surveyed on their RS and G attachment styles, trust in, satisfaction with, and commitment to their service provider, as well as their willingness-to-recommend this provider. Findings emerge from econometric parallel mediation analyses. Results show that customers’ RS but not G attachment style biases their appraisal of trust in, satisfaction with, and commitment to the service provider, which in turn affects their WtR. More specifically, across the four service industries, customers scoring higher on RS anxiety and/or avoidance show systematically lower levels of trust in, satisfaction with, and commitment to the firm, ultimately leading to lower WtR. Firms should especially target customers who score higher on RS avoidance (possibly in combination with higher levels of RS anxiety) as their WtR is strongly biased, which might create uncertainty for other customers about the firm’s reputation.